Limitation on the ownership of foreign parties of real estate in Iceland - Eyvindur G. Gunnarsson (Veftímaritið Stjórnmál og stjórnsýsla, 2012)
According to Article 72, paragraph 2, of the Icelandic Constitution the right of foreign parties to own real property interests or shares in business enterprises in Iceland may be limited by law. Limitation on the ownership of foreign parties of real estate is currently regulated by Law No. 19/1966 on the ownership and use of real estate. The first legislation regarding this matter was Law No. 63/1919 on the same topic. The general rule under current law is that foreign parties, persons and legal entities, may not acquire rights over real estate in Iceland unless they meet stringent requirements regarding residence etc. Parties who enjoy rights under the EEA Agreement, however, enjoy broader rights. The same applies to parties who are authorized to conduct business in Iceland. The article concludes that Law No. 19/1966 should be revised.